Antibody test is not a measure of immunity after Covid-19 vaccination - Ahmad Mahfuz, Gazali (2021)
A news report was published last week about a trio of individuals who reported a negative result from a Covid-19 antibody test. This news caused a stir as people are starting to question the effectiveness of the vaccine.